Chicano students and the courts : the Mexican American legal struggle for educational equality - Valencia, Richard R. (Critical America., 2008)
In 1925 Adolfo "Babe" Romo, a Mexican American rancher in Tempe, Arizona, filed suit against his school district on behalf of his four young children, who were forced to attend a markedly low-quality segregated school, and won. But Romo v. Laird was just the beginning. Some sources rank Mexican Americans as one of the most poorly educated ethnic groups in the United States. Chicano Students and the Courts is a comprehensive look at this community's long-standing legal struggle for better schools and educational equality. Through the lens of critical race theory, Valencia details why